PRECLINICAL ANIMAL TOXICITY STUDIES REPEATED DOSE 28-DAY SUBACUTE ORAL TOXICITY STUDY OF OXY POWDER® IN RATS - Prof. Jogender K. Lalla; Meena U.Shah; Edward F (International Journal of Pharma and Bio Sciences, 2010)
Objectives: 1) To assess the Sub-chronic toxicity of Oxy Powder® administered orally to rats for 28 days, 2) To determine (i) Target organ toxicity (ii) “No observed effect level (NOEL)” (iii) Reversibility of signs of toxicity after recovery period. Background: US FDA does not evaluate safety, efficacy and quality of dietary supplement ingredients or products. GHC decided to study safety of Oxy Powder®, a dietary supplement used in Chronic Constipation and IBS. Guidelines followed: (a) OECD Guidelines No. 407, (b) WHO GCP Guidelines (c) UCSF IACUC POLICY (d) Schedule "Y" in Drugs and Cosmetics Rules, (India). Study Design and Controls: 1) Rats of both sexes in controlled age and body weight were selected. 2) Oxy Powder® was administered at 250, 500 and 1000 mg/kg body weight as aqueous suspensions along with a blank 3) The results were recorded on day 0, throughout the dosing period of 28 days and during recovery period of 14 days End Points: 1) Ophthalmoscopic examination on days 0+29, 2) Haematological analysis, biochemical analysis and urine analysis on days 0+29+43. 3) Organ weights, histopathological and gross pathological observations of sacrificed animals recorded after recovery period. Observations: 1) No abnormalities attributable to the treatment with Oxy Powder® 2) No target organ toxicity 3) No reversibility of any signs of toxicity at the end of recovery period of 14 days. Conclusion: NOEL of Oxy Powder® administered orally to Sprague Dawley rats for 28 days was found to be 1000 mg/kg body weight for male and female animals.